Calculation of the Optimum Cone Angle of a Confuser Used for Reversive-Jet Cleaning of Metal Surfaces against Corrosion - I. V. Kachanov (Nauka i Tehnika, 2019)
The modern industrial production of the Republic of Belarus is characterized by the absence of its own raw material base and significant dependence on imported energy carriers and material resources supplied at world prices. When working in such conditions, production efficiency can be achieved through all-round economy and creation of modern energyand resource-saving technologies. However implementation of such technologies, for example, laser cutting and welding, cladding, flame spraying, painting, etc. directly depends on quality of cleaning metal surfaces from corrosion. Theoretical and experimental studies conducted at the Department of Shipbuilding and Hydraulics of the Belarusian National Technical University have shown that it is very economical to remove corrosion products from metal surfaces using new technology of reverse jet cleaning. The reverse jet cleaning technology is based on a physical principle which presupposes that a jet of working fluid (pulp based on river sand or bentonite clay) rotates 180º when it hits the surface to be cleaned and it leads to an increase in jet impact on the surface to be cleaned by 1.5–2 times due to occurrence of a reactive component. In order to ensure a marked jet reversal an original case design has been developed which is characterized by a patent novelty. One of the main elements in this design is a confuser-shaped stream-forming device. Theoretical investigations on pressure losses of working fluid in a confuser channel which are based on the study of functional at the extremum have made it possible to obtain a dependence for calculation of an optimal cone angle at a turbulent mode of motion within the range of Reynolds numbers 4000 < Re < 3 ×106 while taking into account an influence of working fluid density, its dynamic or kinematic viscosity, average velocity movement of working fluid, confuser radii.